Diagnostic Approach and Treatment of Instestinal Tuberculosis - Murwaningrum, Artati; Abdullah, Murdani; Makmun, Dadang (UI Scholars Hub, 2016)
Tuberculosis (TB) has become a resurgent global problem with increasing numbers of patients. TB infection is still common and remains an important cause of morbidity and mortality, particularly in underdeveloped and developing nations. Intestinal tuberculosis (intestinal TB) rates are rising, consistet with the overall trend. In 2014 Indonesia has the second highest TB prevalence in South East Asia after Timor Leste. Intestinal TB is the sixth highest manifestation of extrapulmonal TB. Manifestations can be non-specific and mimic many conditions, including malignancies causes’ intestinal TB diagnosis more difficult to be accurately determined. Findings from endoscopy and radiological imaging are countless, and depend on the stage of the disease and the time at which investigations are carried out. Hence, diagnosis can be difficult. Until recently there is no single method to identify intestinal TB accurately, various investigative methods have been used to aid in the diagnosis of intestinal TB. Early diagnosis and initiation of antituberculous therapy and surgical treatment are essential to prevent morbidity and mortality. Combined clinical assessment and some modalities examinations are needed to determine intestinal TB. Patient whom has been diagnosed with intestinal TB will be given anti tuberculosis therapy and surgery if any complications occur.